Association of nonalcoholic fatty liver disease and growth hormone deficiency: a systematic review and meta-analysis - Tingting Kong; Yunpeng Gu; Lei Sun; Run Zhou; Jie Li; Junping Shi (Endocrine Journal)
An association exists between nonalcoholic fatty liver disease (NAFLD) and growth hormone (GH). Patients with growth hormone deficiency (GHD) may be more susceptible to NAFLD. The prevalence of NAFLD and nonalcoholic steatohepatitis (NASH) in GHD patients is currently unknown. Multiple databases were searched for experiments related to NAFLD (or NASH) and GHD. Screening, quality evaluation and data extraction were carried out independently by two authors. Analyses used random or fixed effects models, including NAFLD prevalence, NASH prevalence, odds ratio (OR) and 95% confidence interval (CI). We included 10 studies with a total of 782 participants. The results showed that the prevalence of NAFLD in GHD patients was 51% (95% CI: 39–63). The risk of NAFLD in GHD patients was significantly higher than that in controls (age-, sex- or body mass index-matched, without GHD) (pooled OR = 4.27, 95% CI: 1.33–13.68%, p = 0.015). The prevalence of NASH in GHD patients was 18% (95% CI: 5–31). The prevalence of NAFLD in GHD patients is significantly higher than that in the general population, especially NASH. There is a need to develop targeted strategies for the early identification, prevention, or control of NAFLD/NASH in patients with GHD.